Pre-mRNA splicing in the absence of an SR protein RS domain - Zhu, Jun (Cold Spring Harbor Laboratory Press, 2000)
SR proteins are essential pre-mRNA splicing factors that act at the earliest stages of splice-site recognition and spliceosome assembly, as well as later in the splicing pathway. SR proteins consist of one or two RNA-recognition motifs and a characteristic arginine/serine-rich C-terminal RS domain. The RS domain, which is extensively phosphorylated, mediates the subcellular localization of individual SR proteins and also functions as a splicing activation module, apparently by engaging in protein–protein interactions. The RS domain of SF2/ASF is dispensable for the concentration-dependent effects of this SR protein on alternative splice-site selection. However, this RS domain is highly conserved phylogenetically, and was shown to be required for constitutive splicing in vitro and for cell viability. Here, we demonstrate that the RS domain of SF2/ASF is, in fact, dispensable for splicing of several substrates, including constitutive and enhancer-dependent pre-mRNAs. The requirement for this RS domain is substrate specific, and correlates with the strength of the splicing signals. When the 3′ splice site is weak, both the SF2/ASF RS domain and U2AF(35) are required for splicing. These results show the existence of an RS domain-independent function of SR proteins in constitutive and enhancer-dependent splicing, and suggest mechanisms for their role in enhancer function besides U2AF recruitment.